1994
DOI: 10.1002/bip.360340809
|View full text |Cite
|
Sign up to set email alerts
|

Comparative interactions of magnesium and calcium counterions with polygalacturonic acid

Abstract: The comparative interaction of Mgz+ and Ca2+ counterions on carboxyl groups of polygalacturonic acid is developed. Ultracentrifugation, conductimetry, potentiometry, and CD were used in this work. Evidence is provided for a simple electrostatic interaction of Mg*+ counterions; on the opposite side, cooperative interaction of Ca2+ counterions is again demonstrated, causing chain-chain association. 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 36 publications
5
34
0
Order By: Relevance
“…Thus, increased crosslinking due to high Ca 2+ concentration simultaneously makes PI binding energetically less favorable and stiffens the cell wall. This model is supported by findings showing that Ca 2+ binds to HGs in this manner in vitro (Malovíková et al, 2004).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, increased crosslinking due to high Ca 2+ concentration simultaneously makes PI binding energetically less favorable and stiffens the cell wall. This model is supported by findings showing that Ca 2+ binds to HGs in this manner in vitro (Malovíková et al, 2004).…”
Section: Discussionsupporting
confidence: 63%
“…Several previous studies indicate that Ca 2+ cross-links GalUA residues, lending strength to the cell wall (Thibault and Rinaudo, 1985). Although Mg 2+ also interacts with these negative charges, it does not create links between the pectin chains (Thibault and Rinaudo, 1985;Malovíková et al, 2004). Models of the electrostatic charge on the surface of the PI molecule show three partial positive charges associated with tertiary nitrogen atoms that are 6 to 7 Å apart.…”
Section: Discussionmentioning
confidence: 94%
“…The CC theory predicts that a fraction of counterions is confined (condensed) to the immediate vicinity of the polyelectrolyte if its charge density is above critical. This theoretical concept has been confirmed by a series of experiments on a wide variety of polyelectrolytes, counterion species and experimental techniques 3,6,[13][14][15][16][17] . Nevertheless, when two or more counterion species of the same or different valence are present in solution, several experiments, including ours 12,14,17) , have shown that specific interactions, that depend on the polyion/counterion pair, modulate the electrostatic behaviour 6,10,13,14) resulting in a measurable counterion selectivity.…”
Section: Introductionmentioning
confidence: 78%
“…The mechanism or process underlying this darkening is not clear at present. In contrast, deprivation of K or Mg, which are not involved in pectin cross-linking (Malovíková et al 2004), did not cause Evans blue uptake (Fig. 2a), ROS accumulation or root tip darkening (data not shown).…”
Section: Short-term Boron Deprivation Caused Cell Death In Roots Of Amentioning
confidence: 86%
“…2a). Magnesium ions interact with pectin carboxylic acid groups ionically but not coordinately; thus, they cannot participate in forming interchain cross-links in pectin (Malovíková et al 2004). Monovalent K + also does not cross-link pectin.…”
Section: Discussionmentioning
confidence: 99%